Does social software increase labour productivity? - Miruna Sarbu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Social software applications such as wikis, blogs or social networks are being increasingly applied in firms. These applications can be used for external communication as well as knowledge management enabling firms to access internal and external knowledge. Firms can optimize customer relationship management, marketing and market research as well as project management and product development resulting in potential productivity gains for the firms. This paper analyses the relationship between social software applications and labour productivity. Using firm-level data of 907 German manufacturing and service firms, this study examines whether these applications have a positive impact on labour productivity. The analysis is based on a Cobb-Douglas production function. The results reveal that social software has a negative impact on labour productivity. They stay robust for different specifications and alternative measures for social software.
urn:nbn:de:bsz:180-madoc-341336
Keywords: L10; M20; O33; 330; social software; web 2.0; social software intensity; labour productivity